New and little known Coleophora Hübner, 1822 species from Morocco. Part I. (Lepidoptera, Coleophoridae) - Tabell, Jukka; Kullberg, Jaakko; Mutanen, Marko; Tokár, Zdenko; Sihvonen, Pasi (Zootaxa, 2023)
Altogether, 64 Coleophora (Lepidoptera: Coleophoridae) species from Morocco are reported, based on recent collecting expeditions. Twelve new species are described: C. retusa Tabell, sp. nov., C. afrofrischella Tabell, sp. nov., C. olei Tabell, sp. nov., C. carsteni Tabell, sp. nov., C. ifranensis Tabell & Kullberg, sp. nov., C. jaskai Tabell, sp. nov., C. submendica Tabell, sp. nov., C. adipella Tabell, sp. nov., C. antiatlasella Tabell, sp. nov., C. dikeratella Tabell & Kullberg, sp. nov., C. afrodianthi Tabell, sp. nov. and C. knudi Tabell, sp. nov. Of the previously described species, 20 are collected for the first time from Morocco, of which nine are also new to Africa. Adult males and females and their genitalia are illustrated. DNA barcodes of the presented species, if existing, are compared with those of all other Coleophoridae available on the BOLD database. Each of the barcoded new species has a unique BIN (Barcode Index Number). The female genitalia of C. arefactella Staudinger, 1859, C. stenidella Toll, 1952 and C. griseomixta Toll, 1960 are illustrated for the first time.